2020
DOI: 10.1186/s12917-020-02558-2
|View full text |Cite
|
Sign up to set email alerts
|

An integrated review of the role of communication in veterinary clinical practice

Abstract: Background There is a growing interest in exploring the nature of communication in veterinary medicine and understanding how veterinary practitioners communicate with their clients and other professionals. This is the first integrative review of literature on veterinary communication. Applying the PRISMA model, the PubMed, PsychInfo and ERIC databases were searched using keywords such as ‘veterinary’, ‘vet’, ‘communication’ and ‘interaction’ for related articles published between 1 January 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…All professions may benefit from clearer learning objectives and definitions of roles and division of responsibilities by learning together in an interprofessional training setting, which better reflects the real world. The need for implementing communication skills in the veterinary curriculum has been previously demonstrated by several studies [ 14 , 16 , 23 , 25 , 29 31 ] and should explicitly be implemented in German veterinary curricula with longitudinally increasing depth [ 32 ]. Even one-off communication training using role-playing can significantly improve students’ communication skills [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All professions may benefit from clearer learning objectives and definitions of roles and division of responsibilities by learning together in an interprofessional training setting, which better reflects the real world. The need for implementing communication skills in the veterinary curriculum has been previously demonstrated by several studies [ 14 , 16 , 23 , 25 , 29 31 ] and should explicitly be implemented in German veterinary curricula with longitudinally increasing depth [ 32 ]. Even one-off communication training using role-playing can significantly improve students’ communication skills [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interprofessional education can potentially reduce hierarchical structures, perceived misconceptions about other professions, develop students’ awareness of the importance of effective communication in the veterinary team and reduce professional isolation [ 13 ]. Furthermore, effective interprofessional communication will have a positive influence on the clients’ satisfaction with the veterinarian services and their pet’s healthcare [ 31 ]. Although more research is needed to verify its effectiveness [ 6 ], the potential of interprofessional education is considered very high [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible contributor to strained communication over telephone could be the loss of subtle interactions which normally punctuate person to person communication. Previous research has suggested that non-verbal communication may be particularly important in veterinarian–client relationships [ 20 ], and this would often have been lost during teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…In English-speaking countries, the Calgary-Cambridge consultation model is adopted in veterinary colleges, but this does not happen in many other countries. The need for post-educational training in clinical communication skills has also been emphasized (McDermott, 2018;Pun, 2020). The Calgary-Cambridge model, adapted for veterinary use, is the primary model through which the skills required for conducting and communicating within a veterinary consultation are taught in both the undergraduate curriculum and in continuing professional development (McDermott, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent integrated review of the role of communication in veterinary clinical practice (Pun, 2020), it was pointed out that there is a gap of knowledge in this field since limited studies have taken a holistic approach to the role of communication in veterinary practices, by exploring the interactions between veterinarians, clients, and other related professionals.…”
Section: Introductionmentioning
confidence: 99%